1978
DOI: 10.1002/cpt1978233309
|View full text |Cite
|
Sign up to set email alerts
|

High plasma nortriptyline levels in the treatment of depression. I

Abstract: Following a 3-day single-dose kinetic study, 21 moderate to severely depressed inpatients were treated with 100 mg of nortriptyline nightly. Eighteen patients completed the 4-wk trial. The severity of depression was measured by weekly Hamilton Rating Scale and global rating. Blood for plasma nortriptyline estimation was taken at weekly intervals 12 h following the nighttime dose. There was a 6-fold variation in mean plasma nortriptyline levels, ranging from 120 microgram/L to 681 microgram/L. Patients with hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

1978
1978
2011
2011

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 65 publications
(15 citation statements)
references
References 4 publications
1
14
0
Order By: Relevance
“…Subsequent studies have confirmed this finding of an upper therapeutic limit lying between 600-800 nM (30)(31)(32)(33). It has been speculated that NT acts as a postsynaptic blocker of monoamine receptors at high concentrations (29).…”
Section: Introductionsupporting
confidence: 63%
See 1 more Smart Citation
“…Subsequent studies have confirmed this finding of an upper therapeutic limit lying between 600-800 nM (30)(31)(32)(33). It has been speculated that NT acts as a postsynaptic blocker of monoamine receptors at high concentrations (29).…”
Section: Introductionsupporting
confidence: 63%
“…Another similar study found very few circulatory signs, apart from one subject who developed a first degree heart block at NT concentratiohs between 760-1000 nM (11). Serious AE seen at high concentrations in other studies are first degree heart block at 1000 nM (30) and confusion at 1200 nM (33). Two more benign AE which still can be very disturbing to the patient are saliva hyposecretion and accommodation disturbances.…”
Section: Introductionmentioning
confidence: 99%
“…This curvilinear dose-response curve with nortriptyline is a well-established phenomenon replicated in several, fixeddose, follow-up studies 10 including those by Ziegler et al 7 and Montgomery et al 11,12 At the time, the explanation for this finding involved a therapeutic ''plateau'' being reached, above which nortriptyline began antagonizing adrenergic receptors and thereby blocking the antidepressant response observed at lower concentrations. 13 Based on pharmacokinetic data, CYP 2D6 PMs will develop a 3-to 10-fold higher nortriptyline concentration than CYP 2D6 EMs.…”
Section: The Case For Nortriptylinementioning
confidence: 88%
“…1971; Kragh-S6rensen etal. 1973; Ziegler et al 1976;Montgomery et al 1978). NT is considered to Offprint requests to R. Malmgren be a fairly selective NE uptake inhibitor (Carlsson et al 1969a).…”
mentioning
confidence: 99%